2019
DOI: 10.3389/fimmu.2019.01060
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Activating Receptor 1 (DCAR1) Associates With FcεRIγ and Is Expressed by Myeloid Cell Subsets in the Rat

Abstract: Dendritic cell activating receptor-1 (DCAR1) is a cell-surface receptor encoded by the Antigen Presenting Lectin-like gene Complex (APLEC). We generated a mouse monoclonal antibody against rat DCAR1, and used this to characterize receptor expression and function. Rat DCAR1 was expressed on minor subsets of myeloid cells in lymphoid tissue, but was uniformly expressed at a high level by eosinophils, and at a low level by neutrophils. It was expressed by eosinophils in the peritoneal cavity and the lamina propri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The production of a monoclonal antibody for rat Clec4b is described in recently published data from Daws et al [18]. They also detailed how Clec4b is expressed mainly on CD4 + DC/monocytes [18]. We found that Clec4b was only expressed in Clec4b E3 CD4 + DCs but not in B or T cells ( Fig 3F).…”
Section: The Cd4 + Clec4b + Cell Population Consists Of Two Distinct supporting
confidence: 63%
See 2 more Smart Citations
“…The production of a monoclonal antibody for rat Clec4b is described in recently published data from Daws et al [18]. They also detailed how Clec4b is expressed mainly on CD4 + DC/monocytes [18]. We found that Clec4b was only expressed in Clec4b E3 CD4 + DCs but not in B or T cells ( Fig 3F).…”
Section: The Cd4 + Clec4b + Cell Population Consists Of Two Distinct supporting
confidence: 63%
“…Lower levels of Clec4b were observed in pDCs, albeit without any strain difference ( Fig 2D). A recent study by Daws et al [18] supports both of these findings, suggesting that rat Clec4b is highly expressed in CD4 + myeloid cells but not in CD4 + pDCs.…”
Section: Plos Geneticsmentioning
confidence: 78%
See 1 more Smart Citation
“…Fluorescently activated cell sorted splenic neutrophils ( Figure 2 B) were found to express readily Clec4b at a steady-state level. Using a rat Clec4b specific monoclonal antibody (clone: Wen41) [ 28 ], we confirmed by flow cytometry the protein expression on neutrophils ( Figure 2 C). We have earlier shown that the expression of Clec4b on CD4+ dendritic cells are regulating the activation of autoreactive T cells [ 23 ] but since the strongest expression is on neutrophils that play an important role in the development of arthritis [ 29 , 30 ], we now suggest an additional Clec4b-mediated neutrophil function.…”
Section: Resultsmentioning
confidence: 75%
“…Endogenous (host) XCL1 is secreted predominantly by natural killer (NK) cells in the early innate response as well as by CD8 + T cells in the adaptive phase, and it induces chemotaxis only in XCR1expressing dendritic cells (DCs) that are likely to represent conventional dendritic cells 1 (cDC1; Daws et al, 2019;Guilliams et al, 2014;Voisine et al, 2002). XCR1 is predominantly co-expressed on CD8a + mouse cDC1, CD141 + human cDC1 and CD4 − rat DCs, and has been suggested as a lineage marker to phenotype antigen crosspresenting DCs since XCR1 + DCs are involved in the induction of cytotoxic CD8 + T cell responses (Crozat et al, 2010;Gurka et al, 2015;Kroczek and Henn, 2012).…”
Section: Introductionmentioning
confidence: 99%